Dead wood characteristics influencing macrofungal diversity in fragmented forest - Eddy Warman, Nurul Kamaliah (2018)
Macrofungal has a significant role in forest ecosystem by decomposing wood and organic matter. This study was done to examine the abundance and richness of macrofungal substrates, size of dead wood and position of dead wood that influence macrofungal diversity in four fragmented and contiguous forests: Ayer Hitam Forest Reserve (AHFR), Bukit Cherakah Forest Reserve (BCFR), Bangi Forest Reserve (BFR) and Sungai Lalang Forest Reserve (SLFR). Macrofungal identification using macrofungal identification guideline was used to identify macrofungal specimen. ANOVA one-way test, SIMPER and ANOSIM were used for statistical analysis. It was found that, in all study areas, there were 13 types of substrates namely branch, dead trunk, fallen dead tree, fallen leaves, fauna’s habitat, fruit shell, living tree, palm frond, soil, standing dead tree, stump, twig and wood debris. All study areas did not show significant result of substrate abundance and richness on macrofungal diversity. Size and position of dead wood are important factors to measure the macrofungal diversity. Size of dead wood is classified under three classes; Class 1 (diameter of dead wood less than 2.5 cm), Class 2 (diameter of dead wood between 2.5 cm to 15 cm) and Class 3 (diameter of dead wood more than 15 cm). Other than size of dead wood, position of dead wood such as vertical position and horizontal position is also used in measuring macrofungal abundance and richness in four study areas. It was concluded that, fragmented and contiguous forests are similar in terms of its substrate abundance and substrate richness to different study areas.